Hate Speech in Tiktok Comments in the First Debate of the 2024 Vice Presidential Candidates - Ahmad Rifi Nanda Purnama; Urida, Afiatul; Suroya, Rizky Novia (J-LELC: Journal of Language Education, Linguistics, and Culture, 2024)
Hate speech is common on social media today. The advancement of technology is the reason why people pursue the freedom of opinion and the delivery of information that is not necessarily true. This study aims to describe some of the hate speeches that occurred during the 2024 presidential democratic party. More precisely, the researchers took data from netizen comments after the first debate of the 2024 vice president candidate. The method in this research uses qualitative descriptive with a pragmatic approach. The data used is a netizen's comment that contains hate speech on social media tiktok. The data-gathering technique uses logging and documentation. The technique analyzes the data by classifying what kind of hate speech it belongs to after explaining what it means. The results of this study revealed forms of hate speech that were found, among other things, insulting, provoking, and polluting the good name of a 2024 Vice President candidate. Based on the analysis of data on hate speeches on netizen comments on tiktok, researchers found data that was intended to harm a person's good name and honour and could lead to social conflict.